Evaluacion del desempeno del riego con indicadores comparativos: el caso del Distrito de Riego Alto Rio Lerma, Mexico. In SpanishAssessing irrigation performance with comparative indicators: the case of the Alto Rio Lerma Irrigation District, Mexico - Kloezen, W.H.; Garcés-Restrepo, C. (International Water Management Institute, 1998)
Describes and evaluates the application of IWMI's minimum set of performance indicators to the Alto Rio Lerma Irrigation District, and compares this with the application of a small set of process performance indicators.